(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Bangladesh is facing severe problem in using 80-100 penetration grade bitumen for flexible pavement construction due to its high temperature susceptibility, e.g. lower penetration index, insufficient viscosity and lower moisture resistance. To improve these properties bitumen modification is essential. Present work describes the modification of general 80-100 penetration grade bitumen by incorporating natural rubber latex and an organic polymeric additive, polyaniline. Mixing parameters, such as amounts of natural rubber and polyaniline, mixing time and temperature and stirring speed were controlled and investigated carefully. Six bituminous aggregate binders were prepared by varying amounts of natural rubber latex into bitumen by wet process. Physical tests, e.g. penetration, softening point, ductility and viscosity were performed on all samples and compared with unmodified base bitumen. Modified bitumen samples showed better properties compared to ordinary 80-100 penetration grade bitumen. Spectral, thermal and scanning electron microscopic tests were performed on control and bitumen-natural rubber-polyaniline blend samples. Result showed better mixing efficiency of the constituents and thus improved physical, thermal and anti-stripping properties suitable for paving application in Bangladesh and like countries. All findings were discussed in details. Bangladesh J. Sci. Ind. Res.54(4), 307-320, 2019